Implementing genotype-guided antithrombotic therapy - Seip, Richard L (2010)
Genotyping has the potential to improve the efficacy and safety of major antithrombotic drugs. For warfarin, the stable maintenance dose varies from 1–10 mg/day. The VKORC1 −1639G>A allele and the CYP2C9*2 and *3 alleles (cumulative frequency: 90% in Asians, 65% in Europeans and 20% in Africans), explain 45% of response variability in European and 30% in African populations. The large clinical trials COAG and EU-PACT will define the extent to which pharmacogenetic dosing affects the safety and efficacy of warfarin and coumarin derivatives. The platelet inhibitor clopidogrel requires activation by the CYP2C19 enzyme. CYP2C19*2 and *3 alleles (cumulative frequency: 20–50%) produce null enzyme activity, and their presence attenuates platelet inhibition and increases cardiovascular events. The US FDA-mandated drug labeling recognizes the relevance of genotyping in the selection and dosing of both warfarin and clopidogrel.